Aplikasi Manajemen Konflik dalam Suatu Perusahaan atau Organisasi - Munawar, Siti Asiyah (Ali Muchasan, 2015)
Conflict is something that can’t be avoided in life. So it is with organizational life. Conflict management including a process-oriented approach that leads to a form of communication. Conflict management is not only a theory but also needs to be applied and applied maximally so it becomes functional. There are three conflict management strategies that are 1) losing-losing conflict management strategies, 2) win-lose conflict management strategies, and 3) win-win conflict management strategies.